Simultaneous GLP-1 receptor activation and angiotensin receptor blockade increase natriuresis independent of altered arterial pressure in obese OLETF rats. Issue 10 (October 2018) - Rodriguez, Ruben; Moreno, Meagan; Lee, Andrew; Godoy-Lugo, Jose; Nakano, Daisuke; Nishiyama, Akira; Parkes, David; Awayda, Mouhamed; Ortiz, Rudy
Abstract Obesity is associated with an inappropriately activated renin–angiotensin–aldosterone system, suppressed glucagon-like peptide-1 (GLP-1), increased renal Na+ reabsorption, and hypertension. To assess the link between GLP-1 and angiotensin receptor type 1 (AT1 ) signaling on obesity-associated impairment of urinary Na+ excretion (UNa V) and elevated arterial pressure, we measured mean arterial pressure (MAP) and heart rate by radiotelemetry and metabolic parameters for 40 days. We tested the hypothesis that stimulation of GLP-1 signaling provides added benefit to blockade of AT1 by increasing UNa V and further reducing arterial pressure in the following groups: (1) untreated Long–Evans Tokushima Otsuka (LETO) rats (n = 7); (2) untreated Otsuka Long–Evans Tokushima Fatty (OLETF) rats (n = 9); (3) OLETF + ARB (ARB; 10 mg olmesartan/kg/day;n = 9); (4) OLETF + GLP-1 receptor agonist (EXE; 10 µg exenatide/kg/day;n = 7); and (5) OLETF + ARB + EXE (Combo;n = 6). On day 2, UNa V was 60% and 62% reduced in the EXE and Combo groups, respectively, compared with that in the OLETF rats. On day 40, UNa V was increased 69% in the Combo group compared with that in the OLETF group. On day 40, urinary angiotensinogen was 4.5-fold greater in the OLETF than in the LETO group and was 56%, 62%, and 58% lower in the ARB, EXE, and Combo groups, respectively, than in the OLETF group. From day 2 to the end of the study, MAP was lower in the ARB and Combo groups than in the OLETF rats. These results suggest that GLP-1 receptor activation may reduce intrarenal angiotensin II activity, and that simultaneous blockade of AT1 increases UNa V in obesity; however, these beneficial effects do not translate to a further reduction in MAP.